2020
DOI: 10.3389/fneur.2020.01054
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Glial Fibrillary Acidic Protein (GFAP) in Serum and Plasma Following Mild Traumatic Brain Injury in Older Adults

Abstract: Conclusions: Despite differences in concentration, serum and plasma GFAP levels were highly correlated and had similar discriminability between those with and without intracranial abnormalities on head CT following an mTBI. Neither serum nor plasma GFAP had adequate discriminability to identify patients who would have poor functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 47 publications
(88 reference statements)
1
37
0
1
Order By: Relevance
“…It should also be considered that, in Verberk et al, GFAP was measured in serum, as opposed to plasma in the present study. So far, only one study has compared plasma and serum concentrations of GFAP in a traumatic brain injury cohort, with good correlation but significantly higher concentrations of GFAP in plasma [ 19 ]. Extensive head-to-head comparisons are yet to be done between the two different methods of analysis and it cannot be excluded that the presence of clotting agents in the sample might affect the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be considered that, in Verberk et al, GFAP was measured in serum, as opposed to plasma in the present study. So far, only one study has compared plasma and serum concentrations of GFAP in a traumatic brain injury cohort, with good correlation but significantly higher concentrations of GFAP in plasma [ 19 ]. Extensive head-to-head comparisons are yet to be done between the two different methods of analysis and it cannot be excluded that the presence of clotting agents in the sample might affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Glial fibrillary acidic protein (GFAP) is expressed in the cytoskeleton of astrocytes and has been found significantly increased in CSF in AD and other neurodegenerative diseases compared to healthy controls [12][13][14][15]. GFAP has also been recently measured in plasma and serum, where it was found increased in different neurological conditions, including AD [16][17][18][19][20][21][22][23][24]. Different studies have shown that higher concentrations of plasma GFAP were associated to amyloid-PET positivity and worse outcomes in global cognition [22,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, tau, is present in unmyelinated axons of neurons, but also in astrocytes and oligodendrocytes, which may explain why low serum concentrations indicate little or no injury (or astrocytic upregulation) [ 45 ]. All three markers are currently studied as prognostic markers within various neurological conditions and may soon become widely available [ 30 , 31 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glial brillary acidic protein (GFAP) is expressed in the cytoskeleton of astrocytes and has been found signi cantly increased in CSF in AD and other neurodegenerative diseases compared to healthy controls (12)(13)(14)(15). GFAP has also been recently measured in plasma and serum, where it was found increased in different neurological conditions, including AD (16)(17)(18)(19)(20)(21)(22)(23)(24). Increase of plasma GFAP in AD patients was associated to amyloid-PET positivity and worse outcomes in global cognition (22,24,25).…”
Section: Introductionmentioning
confidence: 99%